Curriculum Improvement for Better Indonesian Education: A Reconstructed Philosophy of Education Revisited - Udin Saripudin Winataputra; Riza Al Rakhman (International Conference on Education and Language (ICEL), 2013)
It is generally accepted that curriculum can be considered as aprogressively modifiable ideas, plan, and reality. For Indonesian education to catch up with current scientific and tehnological progresses as well as changing Indonesian society’s needs,  the central government’s efforts to continually improve the school curricula have been undergone recently. It is hoped the new curricula would be able to fullfill the Middle Range National Development Plan mision which call for revisiting all the better thoughts and efforts to improve the existing 2006 school-based curricula or the KTSP (Kurikulum Tingkat Satuan Pendidikan) curricula.This article analyzes foundational ideas and principles which could explain the why, what, how the improvement of the existing curricula are urgently needed. Conceptual analysis will be applied  to look into all national foundational imperatives which call for improving school curricula as well as asking all national education stakeholders to enhance both national concern and collaboration for the bettermen of future Indonesian generation through building and implementing quality education, primarily that for schools.